THE IMPACT OF THE TRAINER’ COMMUNICATIONAL STYLE ON ADULT LEARNERS ‘LEARNING STYLES - Urea, Ionela Roxana; Pirvu, Cristina Cora (International Journal of Research -GRANTHAALAYAH, 2020)
Today, it is clear to everyone that regardless of the studies completed, the process of continuous improvement is necessary depending on the field in which they work. Each country has designed specific strategies in the field of adult education, as part of lifelong learning. Our research had the aim to highlight, beyond the type of training program for adults, the relationship between the communication style of trainers involved in adult education and the learning style of adult learners. In our research we used: a) the “Questionnaire S.C. (Analysis of Communication Style) b) the Romanian version of “Learning style Questionnaire”; c) non-directive interviews; d) statistical processing methods. The results that came from the data allow us to see the influences of the trainers’ communicational style upon the learning style of adult learners during the training sessions. The conclusions are significant for developing proper vocational counselling programs for trainers that are involved in training adult learners.